The dialectical alterity of Kierkegaardian freedom - Binetti, María José (Estudios de Filosofía, 2012)
The aim of this article is to show, inside Kierkegaardian's Freedom, the presence of an active alterity, conceived as difference, non-being, nothingness, which are able to impel the existence, through the force of contradiction, to constitute its own identity. For Kierkegaard this radical alterity is sin, whose conscience reveals to man both his essential duality and the distance that separates him from the absolute being.